Integrated omics analysis of PGPR and AMF effects on soil microbiota and root metabolites in Isatis indigotica - Yang, Shuai; Yuan, Ting; Duan, Tingting; Zhu, Huimin; Zhang, Xiaoxia; Zhang, Haihong; Jiang, Junjie; Yang, Jun; Hu, Lichuan; Yu, Yu; Zhang, Lijun; Yuan, Zhaodi (Frontiers in Microbiomes, 2025)
IntroductionThe intensive use of chemical fertilizers and pesticides in modern agriculture has led to severe soil degradation and environmental pollution, which threatens the long-term production of crops. Plant growth-promoting rhizobacteria (PGPR) and arbuscular mycorrhizal fungi (AMF) are promising biofertilizers which can boost plant growth and improve soil quality. However, the combined effects of these factors on medicinal plants such as Isatis indigotica remain unclear.MethodsThis study isolated and identified six plant growth-promoting rhizobacteria (PGPR) strains (Acinetobacter sp. and Bacillus albus) from the rhizosphere of Isatis indigotica. A pot experiment was conducted with control, PGPR inoculation and AMF+PGPR co-inoculation treatments to assess the effects of these treatments on the growth of Isatis indigotica and its soil physicochemical properties. High-throughput sequencing was used to analyse the structure of the rhizosphere microbial community, while non-targeted metabolomics was employed to profile root metabolites. Finally, a redundancy analysis (RDA) was performed to reveal the correlations between the key microbial taxa and the differential metabolites.ResultsAll six of the isolated PGPR strains exhibited multiple capacities that promote plant growth. The pot experiment demonstrated that both PGPR inoculation and AMF+PGPR co-inoculation significantly increased the height and root length of Isatis indigotica compared to the control, while also enhancing the soil’s SOC, TN and AP content. Analysis of the microbial community revealed that the inoculation treatments enriched the rhizosphere microbiome with beneficial taxa such as Proteobacteria and Ascomycota. Metabolomic analysis revealed that inoculation treatments significantly increased the concentrations of key bioactive compounds, such as flavonoids, lipids and amino acids. Furthermore, the RDA revealed a strong correlation between the accumulation of various root metabolites (e.g., benzenesulfonic acids, carbohydrates and fatty acids) and dominant microbial genera (e.g., Acinetobacter, Paenibacillus and Botryotrichum).ConclusionsPGPR and AMF improve the uptake of nutrients and the synthesis of secondary metabolites in Isatis indigotica by altering the structure of the rhizosphere microbiome and root metabolomes. These findings support the use of PGPR and AMF as biofertilizers for sustainably cultivating medicinal plants.